Peran Kepemimpinan Transformasional Dalam Meningkatkan UMKM Di Kota Medan - Bertha Nerphy Siahaan; Muridha Hasan; Choncho Reynols Manday; Durahman Marpaung (Institut Nalanda, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as the backbone of economic stability in Medan City. However, most business actors still face growth stagnation due to weak managerial capacity and slow business adaptation in the digital era. This study aims to analyze the empirical effect of transformational leadership on the organizational performance of MSMEs in Medan City. Using a quantitative approach with a causal associative method, data were gathered from 150 respondents across the culinary, trade, services, and creative industry sectors, selected through a purposive sampling technique. Data collection was carried out by distributing Likert-scale questionnaires and analyzed using simple linear regression assisted by IBM SPSS Statistics. The results indicated that all instruments were valid, reliable, and met the requirements of classical assumption tests. Partial hypothesis testing (t-test) proved that transformational leadership has a positive and significant effect on MSME organizational performance, with a t_statistic value of 8.412 (p = 0,000< 0.05). The coefficient of determination (R2) analysis showed that transformational leadership contributes 32.4% to the variation in organizational performance. These findings confirm that a visionary, inspirational, and adaptive leadership approach serves as a crucial internal foundation to drive innovation and business sustainability for urban economies amid intensifying digital competition.